Pengaruh Kualitas Produk, Lokasi, Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Savio Coffee and Eatery - Dhea Nanda; Ricky Talumantak (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to determine the effect of product quality, location, service quality, and on purchasing decisions at Savio Coffee end Eatery. The study conducted at Savio Coffee And Eatery involved 120 respondents who made purchases at the establishment. The data was collected through questionnaires, and the results of the multiple linear regression analysis showed a positive correlation between product quality, location, service quality, and purchasing decisions. This method of data collection is reliable, and it's fascinating to see how can be utilized to analyze this data.